Observation of B[bar]→D(∗)π+π-l[iota]-v[bar] decays in e+e- collisions at the [upsilon](4S) resonance - Lees, Jean-Pierre; Adametz, Aleksandra; Uwer, Ulrich (Physical review letters, 2016)
We report on measurements of the decays of ¯B mesons into the semileptonic final states ¯B→D(*)π+π−ℓ−¯ν, where D(*) represents a D or D∗ meson and ℓ− is an electron or a muon. These measurements are based on 471×106 B¯B pairs recorded with the BABAR detector at the SLAC asymmetric B factory PEP-II. We determine the branching fraction ratios R(*)π+π−=B(¯B→D(*)π+π−ℓ−¯ν)/B(¯B→D(*)ℓ−¯ν) using events in which the second B meson is fully reconstructed. We find Rπ+π−=0.067±0.010±0.008 and R∗π+π−=0.019±0.005±0.004, where the first uncertainty is statistical and the second is systematic. Based on these results and assuming isospin invariance, we estimate that ¯B→D(*)ππℓ−¯ν decays, where π denotes either a π± and π0 meson, account for up to half the difference between the measured inclusive semileptonic branching fraction to charm hadrons and the corresponding sum of previously measured exclusive branching fractions.